2018
DOI: 10.3389/fimmu.2018.00838
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Activation: The Ang/Tie Axis in Sepsis

Abstract: Sepsis, a dysregulated host response to infection that causes life-threatening organ dysfunction, is a highly heterogeneous syndrome with no specific treatment. Although sepsis can be caused by a wide variety of pathogenic organisms, endothelial dysfunction leading to vascular leak is a common mechanism of injury that contributes to the morbidity and mortality associated with the syndrome. Perturbations to the angiopoietin (Ang)/Tie2 axis cause endothelial cell activation and contribute to the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 218 publications
(316 reference statements)
1
97
0
3
Order By: Relevance
“…Vascular endothelial cells lining in the inner side of vascular system play a significant role in maintaining vascular homeostasis. In the early stage of sepsis, excessive release of pro‐inflammatory cytokines and the adhesion of leucocytes disrupt endothelial cell integrity and eventually lead to vascular leakage, disturbance of blood flow and sepsis‐induced organ failure . In severe infections and sepsis, persistent vascular damage and leakage can contribute to tissue hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular endothelial cells lining in the inner side of vascular system play a significant role in maintaining vascular homeostasis. In the early stage of sepsis, excessive release of pro‐inflammatory cytokines and the adhesion of leucocytes disrupt endothelial cell integrity and eventually lead to vascular leakage, disturbance of blood flow and sepsis‐induced organ failure . In severe infections and sepsis, persistent vascular damage and leakage can contribute to tissue hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial-specific angiopoietin (Ang)-tyrosine kinase (Tie) system has been considered as an important mechanism in regulating endothelial activation of sepsis and as a possible determinant of injury severity. 18 Angiopoietin 1 (Ang1) is released by pericytes, and it enhances the stability of formed vessels by binding to its receptor Tie2 in endothelial cells. 19 Ang2 is stored in Weibel-Palade bodies in endothelial cells.…”
mentioning
confidence: 99%
“…In a non-disease state, there is a higher concentration of circulating Ang-1 than Ang-2 promoting microvascular quiescence. During malaria infection, Ang-2 and vWF are released from Weibel-Palade bodies (WPB) within the endothelial cells, antagonizing Tie-2 activation and triggering a pro-coagulant and pro-inflammatory state, associated with microvascular activation and a risk of SM, reviewed in [79]. Hence, the ratios of Ang-1 and Ang-2 are indicative of endothelial dysregulation, where higher Ang-2 and lower Ang-1 levels indicate progression to severe and potential fatal disease [80].…”
Section: Endothelial Activationmentioning
confidence: 99%
“…This study showed that even after the initiation of microvascular leak as determined by Evan's blue dye extravasation into the brain parenchyma, agents such as BowAng1, can prevent further brain injury and death compared to artesunate alone. More therapeutic interventions targeting the Ang-1/Tie-2 axis are reviewed in [79]. Likewise, the heme axis is a potential intervention point that remains to be explored.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
See 1 more Smart Citation